Pengembangan Alat Peraga Biologi Berbasis Instgarm Terintegrasi Nilai- Nilai Keislaman Pada Materi Sistem Peredaraan Darah Manusia Kelas XI - Allia Nur Aliffah; Achmad Ali Fikri; Setiati Hidayah (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
This research uses Research and Development (RnD) research, with a 4D development model. This research aims to find out how the product is developed and the level of feasibility through media, material and Islamic validation as well as the practicality of teachers and students. Data collection techniques for product development are through observation, interviews, questionnaires and documentation. Next, the data obtained was analyzed using quantitative descriptive analysis. This research produces a product in the form of an Instagram-based biology teaching aid integrated with Islamic values ​​in the human circulatory system material. This product meets the valid and practical criteria by obtaining a validity assessment of 88.84% in the